Mid-infrared optical properties of pyrolytic boron nitride in the 390–1050 °C temperature range using spectral emissivity measurements. (June 2017) - González de Arrieta, I.; Echániz, T.; Fuente, R.; del Campo, L.; De Sousa Meneses, D.; López, G.A.; Tello, M.J.
Abstract: This paper shows a systematic experimental and theoretical study on the temperature dependence of the infrared optical properties of pyrolytic boron nitride (pBN), from 390 to 1050 °C for wavelengths between 4 and 16 μm. The temperature dependence of these properties has never been analyzed before. The measured emissivity spectra were fitted to a dielectric function model and an effective medium approximation. The phonon frequencies and dielectric constants agreed well with room temperature experimental values from the literature, as well as with ab initio and first principles calculations. In addition, the phonon frequencies of the perpendicular mode and the dielectric constants of the parallel mode showed an appreciable parabolic temperature dependence, which justifies the interest of more theoretical efforts in order to explain this behavior. Finally, the results of this work demonstrate that thermal emission spectroscopy allows obtaining the values of the optical and dielectric parameters of impure ceramic materials in a simple manner as a function of temperature. Abstract : Highlights: The infrared spectral emissivity of a pBN sample from 390 to 1050 °C is presented. Spectra are fitted to a 4-parameter dielectric function model with effective medium approximation. The temperature dependence of the phonon frequencies and dielectric constants is analyzed. A review of experimental and first-principles data from the literature is made. The dielectric functions obtained with the model are compared to a Kramers–Kronig procedure.